Electrochemical Point-of Care (PoC) Determination of Interleukin-6 (IL-6) Using a Pyrrole (Py) Molecularly Imprinted Polymer (MIP) on a Carbon-Screen Printed Electrode (C-SPE) - Gonçalves, M. de Lurdes (2022)
Here is presented a highly sensitive biomimetic sensor for the detection of an Alzheimer’s Disease (AD) biomarker, interleukin-6 (IL6), for point-of-care (PoC) analysis. The imprinted polymeric film was prepared by the co-electropolymerization of pyrrole (Py) and carboxylated pyrrole in the presence of IL6, on a carbon-screen printed electrode . The biomarker molecule was then removed by oxalic acid , creating the recognition vacant sites. Similarly, a control was also prepared in absense of the IL6 biomarker . The different steps of the sensor fabrication were characterized by Raman Spectroscopy, Electrochemical Impedance Spectroscopy (EIS), and Cyclic Voltammetry. Biomarker recognition and capture capacity of the sensing material was measured by EIS. The biomimetic sensor showed a limit of detection for IL6 of 0.02 pg/mL in spiked serum samples. Overall, the biosensing device showed good sensitivity, reproducibility, accuracy, and rapid response time, which contibute for the development of early diagnostics Poc tools for neurological diseases.